2016
DOI: 10.1136/bjsports-2016-096634
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce sedentary behaviour in 0–5-year-olds: a systematic review and meta-analysis of randomised controlled trials

Abstract: Aim or objectiveTo evaluate the effectiveness of behavioural interventions that report sedentary behaviour outcomes during early childhood.DesignSystematic review and meta-analysis.Data sourcesAcademic Search Complete, CINAHL Complete, Global Health, MEDLINE Complete, PsycINFO, SPORTDiscus with Full Text and EMBASE electronic databases were searched in March 2016.Eligibility criteria for selecting studiesInclusion criteria were: (1) published in a peer-reviewed English language journal; (2) sedentary behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 70 publications
2
55
1
1
Order By: Relevance
“…≥6 months in duration) were more effective than shorter duration interventions (i.e. <6 months in duration) . All of these studies that reported on insufficient intervention dose in this study varied in context; no clear determination about the most effective intervention dose in certain contexts could be ascertained from the data collected.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…≥6 months in duration) were more effective than shorter duration interventions (i.e. <6 months in duration) . All of these studies that reported on insufficient intervention dose in this study varied in context; no clear determination about the most effective intervention dose in certain contexts could be ascertained from the data collected.…”
Section: Discussionmentioning
confidence: 79%
“…replacing typical sitting activities or environments with opportunities for children to stand and move around freely) rather than the provision of specific active play opportunities. However, a recent meta‐analysis found that interventions targeting physical activity were more effective at reducing children's objectively measured sedentary time than those specifically targeting children's sedentary time . Given the small number of studies included in both meta‐analyses, it is possible that these findings may be a reflection of the individual studies that were included in each review.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 17 included reviews, six reviews examined intervention effectiveness in children and adolescents across various settings [ 23 , 26 , 27 , 31 , 32 , 35 ], mainly schools and home. Three reviews investigated SB interventions targeting adults in office workplaces [ 24 , 28 , 29 ], whilst the other six reviews explored interventions targeting adults across all settings [ 30 , 34 , 36 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Behaviour outcomes reported in the included reviews were screen time (measured using self-report), sitting time (measured through self-report or device-measured detecting sit-stand posture) and sedentary time (measured by a device such as an accelerometer that detects intensity level). Screen time was the dominant outcome reported in children and adolescent, and it was reported in all seven studies in this age group, with only one study also investigate total sitting time [ 26 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…All interventions with the exceptions of those that were mixed including an active control in the medium-term demonstrated reductions in SB. A recent systematic review of interventions to reduce SB in 0-5 year olds found overall mean reductions in SB of -18.91 min/day; 95% CI -33.31 to -4.51 [197]. This finding suggests that interventions of ≥6 months duration and those conducted in community settings were more effective.…”
Section: Children Interventionsmentioning
confidence: 98%